Activated carbon modified by atomic layer deposition and method thereof

JP7644148B2Active Publication Date: 2025-03-11INGEVITY SOUTH CAROLINA LLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022574585
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-05
Filing Date
2021-06-04
Publication Date
2025-03-11
Estimated Expiration
2041-06-04

Smart Images

  • Figure 0007644148000006
    Figure 0007644148000006
  • Figure 0007644148000007
    Figure 0007644148000007
  • Figure 0007644148000008
    Figure 0007644148000008
Patent Text Reader

Abstract

Provided herein are structures, atomic layer deposition methods for preparing the structures, and apparatus for preparing the structures. The described structures offer unexpected advantages over currently available materials.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of U.S. Patent Application No. 63 / 035,224, filed June 5, 2020, which is incorporated by reference in its entirety.

[0002] The present disclosure, in various aspects and embodiments, relates to active adsorbent materials that have been modified, for example by atomic layer deposition methods, and methods and systems including same. [Background technology]

[0003] In catalyst-driven processes, the reaction rate is often limited by the number of available active sites on the catalyst substrate. As a result, maximization of surface area is an important design aspect of many heterogeneous catalytic systems. One method frequently used to achieve high surface area is by using catalytically active materials (e.g., TiO 2 , SiO 2 , or Al 2 O 3 ) onto a high surface area support material such as activated carbon. 2 is an industrially relevant oxide with a wide range of applications including photocatalysis, catalysts for NOx abatement via selective catalytic reduction (SCR) for stationary power applications, various active metals, pigments and coatings, ceramics, and catalyst supports for various consumer products, to name a few.

[0004] One commonly employed technique for dispersing catalytically active materials onto a support material is solution drop impregnation, whereby the active material is first placed in solution, often in the form of a nitrate (e.g., Ce(NO 3 ) 3) and then added to a porous support where capillary action draws the solution into the porous structure. Once the pores of the support are filled with the solution, the saturated support is dried and calcined to drive off volatile species and deposit the active metal onto the walls of the support. Although this technique is relatively effective in dispersing the active material onto the support structure, it presents some notable drawbacks. First, the particle size is not well controlled, resulting in portions of the active material that cannot be utilized. In addition, there is often poor contact between the deposited active material and the support material, which generally results in crystallization and agglomeration of the active phase, leading to further loss of surface area and active material utilization. Similarly, when the active metal particles are heated, sintering results in larger particles and reduced atomic efficiency. Furthermore, only a portion of the support surface is covered with active material by this technique.

[0005] An alternative technique that has been recently explored to disperse metal particles onto oxide supports is atomic layer deposition (ALD). Compared with conventional catalytic loading of active metal materials onto supports, the advantage of using ALD is that ALD allows for the deposition of metals or metal oxides in a highly dispersed manner, thus improving the atomic efficiency and surface area of ​​the catalytically active metal materials. During ALD, the active metal material is introduced onto the support as a vapor. To provide sufficient vapor pressure, the active metal material is typically prepared in organometallic form. Upon exposure of the support material to the organometallic vapor, the surface of the support is coated with the organometallic precursor until it is saturated. Ideally, the conditions under which the organometallic precursor is adsorbed onto the surface result in a first layer that is partially oxidized and strongly adsorbed onto the surface. After exposure to the organometallic precursor, the support is purged with an inert species or exposed to a vacuum for a period of time to remove the adsorbed multilayer species. At this point, the active metal coated support is exposed to an oxidizing agent such as ozone, water, or baked in air to fully oxidize the adsorbed organometallic species. This stepwise sequence of precursor introduction followed by oxidation is referred to as a single ALD cycle. Given that each cycle consists of the adsorption of only a monolayer of precursor material, the process is essentially self-limiting, yielding at most a single atomic layer per cycle.

[0006] ALD is commonly used for semiconductor device fabrication and has also recently been explored for the synthesis of catalytically active materials. In both of these applications, ALD is performed on a support or substrate material that has functional groups (e.g., oxygen-containing functional groups) attached to its surface, and the oxygen atoms initiate the ALD growth mechanism by partially oxidizing the adsorbed organometallic species. Traditional methods use a carrier gas, such as helium, to deliver precursor gases to the substrate, which was developed by the semiconductor industry to deposit on relatively flat surfaces rather than the highly porous surfaces used, for example, as supports for heterogeneous catalysts. Substrates used in traditional methods for semiconductor fabrication generally have flat surfaces and therefore have a smaller surface area, so the exposure time of the substrate to the precursor gas is very short, allowing for rapid cycling, but often multiple cycles are required because less active metal material is deposited per cycle. To achieve a similar loading, the number of cycles required to modify the surface of a porous (i.e., relatively high surface area) material is much less than a planar semiconductor material, but the diffusion of precursors and oxidants through the porous material limits the rate at which cycles can be performed.

[0007] Because diffusion of precursor gases in and out of the pores of porous substrate materials is slow, the use of a carrier gas, as used in conventional methods, is impractical and leads to increased costs because the precursor gas is blown through the system and not collected. Thus, there is a need in the art for improved catalytically active porous materials and methods for their manufacture. Summary of the Invention

[0008] Described herein are porous structures and methods for their fabrication. It has been surprisingly and unexpectedly discovered that porous materials, such as activated adsorbent materials such as activated carbon, can serve as substrates for ALD.

[0009] Thus, in one aspect, the present specification provides a structure comprising an active adsorbent material, e.g., a porous active adsorbent material, and a metal species deposited thereon. In certain aspects, the present specification also provides a structure comprising a substrate comprising an active adsorbent material and a metal species deposited thereon.

[0010] In an additional aspect, the present disclosure provides a method of preparing a structure by a process that includes: (a) providing an active adsorbent material, e.g., a porous active adsorbent material (e.g., activated carbon), in a reactor; and (b) performing or conducting at least one atomic layer deposition cycle to deposit a metal species, e.g., a metal oxide, the at least one atomic layer deposition cycle including: (i) introducing a first precursor gas into the reactor to provide a metal species precursor; and (ii) introducing a second precursor gas into the reactor to provide the structure. In any aspect or embodiment, step (b) is repeated from 2 to about 10 times.

[0011] In an additional aspect, the present specification provides a structure prepared by atomic layer deposition (ALD) by a process comprising: (a) providing an active adsorbent material, e.g., a porous active adsorbent material (e.g., activated carbon), in a reactor; and (b) performing at least one atomic layer deposition (ALD) cycle to deposit a metal species, e.g., a metal oxide, wherein the at least one atomic layer deposition cycle comprises: (i) introducing a first precursor gas into the reactor to provide a metal species precursor; and (ii) introducing a second precursor gas into the reactor to provide the structure.

[0012] In any aspect or embodiment described herein, the structure prepared by atomic layer deposition (ALD) is a porous metal-coated structure.

[0013] In any aspect or embodiment described herein, the active adsorbent material is a porous active adsorbent material. In any aspect or embodiment described herein, the porous active adsorbent material comprises activated carbon, e.g., porous activated carbon. In any aspect or embodiment described herein, the activated carbon comprises activated carbon powder, granules, pellets, monolith, or honeycomb forms.

[0014] In any of the aspects or embodiments described herein, the metal species comprises at least one metal. The metal species may be derived from a metal species precursor having at least one metal and at least one ligand, which may then be synthetically modified (e.g., oxidized or reduced) to provide the metal species.

[0015] The foregoing general description of utility is given by way of example only and is not intended to limit the scope of the present disclosure and the appended claims. Additional objects and advantages associated with the compositions, methods, and processes of the present invention will be understood by those skilled in the art in view of the claims, description, and examples of the present invention. For example, the various aspects and embodiments of the present invention may be utilized in numerous combinations, all of which are expressly contemplated by this specification. These additional advantages, objects, and embodiments are expressly included within the scope of the present invention. Publications and other materials used to describe the background of the present invention and, in certain cases, to provide additional details regarding the implementation are incorporated by reference.

[0016] The accompanying drawings, which are incorporated in and form a part of this specification, illustrate several embodiments of the present invention and, together with the description, serve to explain the principles of the invention. The drawings are only for the purpose of illustrating one embodiment of the present invention and are not to be construed as limiting the invention. Further objects, features and advantages of the present invention will become apparent from the following detailed description taken in conjunction with the accompanying drawings illustrating exemplary embodiments of the invention. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 shows an exemplary embodiment of an apparatus used for an ALD method. [Diagram 2] Figure 2 shows the results of gravimetric analysis of activated carbon powder modified with titanium oxide after 1–4 cycles of ALD. [Diagram 3] 3A-3D show the wt % of TiO on titanium oxide modified activated carbon powder after 0 ALD cycles (FIG. 3A), 1 ALD cycle (FIG. 3B), 2 ALD cycles (FIG. 3C), and 4 ALD cycles (FIG. 3D). [Figure 4] 4A-4D are scanning electron microscope (SEM) images of titanium dioxide modified activated carbon powder after 0 ALD cycles (FIG. 4A), 1 ALD cycle (FIG. 4B), 2 ALD cycles (FIG. 4C), and 4 ALD cycles (FIG. 4D). [Diagram 5] FIG. 5 shows the TiO2 growth rate over four ALD cycles on titanium oxide modified activated carbon powder. [Figure 6] 6A-6C show 2-propanol temperature programmed desorption (TPD) spectra of unmodified activated carbon powder (FIG. 6A), titanium oxide modified activated carbon powder (FIG. 6B), and P25 TiO2 (FIG. 6C). [Figure 7] Figures 7A-7B show a comparison of the product spectra of acetone (Figure 7A) and propene (Figure 7B) from 2-propanol TPD on activated carbon powder modified with titanium dioxide and P25 TiO2. [Figure 8] FIG. 8 shows an exemplary embodiment of an apparatus used for the ALD method. [Figure 9] 9A-9C show SEM images of virgin commercial carbons WV-A1100 (FIG. 9A), BAX1500 (FIG. 9B), and synthetic graphite (FIG. 9C). [Figure 10] FIG. 10 shows a comparison of the XPS spectra of AG (AQUAGUARD), oxidized RGC, graphite oxide, graphite, RGC, WV-A1100, and BAX 1500 carbon. [Figure 11] A comparison of the estimated surface coverage of coconut, oxidized RGC, RGC, WV-A1100, AG (AQUAGUARD), and graphite is shown in Figure 11. The figure shows that the TiO2 ALD rate is highest for coconut and follows the order coconut > oxidized RGC > Aquaguard > WV-A1100 > RGC > graphite. [Figure 12] 12A-C show SEM images of oxidized RGC, AG, and graphite after two cycles of TiO 2 ALD in the top panels, and the corresponding XRD spectra and EDS maps in the bottom panels. [Figure 13] FIG. 13 shows XPS spectra of WV-A 1100 before and after TiO2 ALD. The virgin material is the bottom trace, the material after one ALD cycle is the middle trace, and the material after two ALD cycles is the top trace. [Figure 14] 14 shows the XPS spectra of coconut, WV-A 1100, and RGC after two cycles of TiO2 ALD, respectively. RGC after two cycles of ALD is the bottom trace, 1100 after two cycles of ALD is the next highest trace, and coconut after two cycles of ALD is the top trace. [Figure 15] FIG. 15 shows the pore size distribution (PSD) of WV-A1100 before and after TiO2 ALD. The virgin material is the top trace, the material after one ALD cycle is the middle trace, and the material after two ALD cycles is the bottom trace. [Figure 16] 16A-16B show the TPD spectra after two cycles of TiO2-ALD for WV-A1100 and RGC, respectively. For each of FIGs. 16A-16B, the spectrum of the ALD modified material is overlaid with the spectrum of virgin material. The lower curves for 2-propanol, acetone, and propene are for virgin material, and the upper curves for each of 2-propanol, acetone, and propene are after two cycles of ALD. [Figure 17] FIG. 17 shows the TPD spectrum of TiO2 modified graphite. [Figure 18] FIG. 18 shows the TPD spectrum of TiO2 modified AQUAGUARD. [Figure 19] FIG. 19 shows the TPD spectrum of TiO2 modified oxidized RGC. [Figure 20] 20A-20C show SEM micrographs and XRD of WV-A 1100 after 1 Pd ALD cycle (FIG. 20A), 2 ALD cycles (FIG. 20B), and 4 ALD cycles (FIG. 20C). [Figure 21] 21 shows the XPS of Pd-modified samples of WV-A 1100 after 1, 2, and 4 cycles of ALD. The bottom trace is virgin material, the next top trace is after 1 cycle of ALD, the next top trace is after 2 cycles of ALD, and the top trace is after 4 cycles of ALD. The peak at 335.8 corresponds to Pd(0). [Figure 22] FIG. 22 shows the wt % Pd deposited on WV-A1100 after 1 cycle (1.29 wt %), 2 cycles (2.84 wt %), and 4 cycles (5.21 wt %) of ALD. [Figure 23] FIG. 23 shows the disappearance of abietic acid over time when it was subjected to a disproportionation reaction. The two overlapping curves are the reaction without catalyst and with virgin material. The bottom curve corresponds to the reaction of abietic acid in the presence of Pd-modified material (i.e., catalyst) obtained after one and two cycles of ALD. The upper curve corresponds to the reaction of abietic acid in the presence of Pd-modified material (i.e., catalyst) obtained after one cycle of ALD. [Figure 24] Figure 24A shows the TGA spectra using air and N2 of the products from the alcohol dehydrogenation reaction of 2-propanol in the presence of Pd deposited on WV-A 1100 catalyst, and Figure 24B shows the TPD spectrum of the evolved gas from the reaction. [Diagram 25] Figure 25A shows an SEM image of graphite after two cycles of Pd ALD at 10,000x magnification, and Figure 25B shows an SEM image of graphite after two cycles of Pd ALD at 100,000x magnification. [Figure 26] Figure 26A shows an SEM image of graphite oxide after two cycles of Pd ALD at 10,000x magnification, and Figure 26B shows an SEM image of graphite after two cycles of Pd ALD at 100,000x magnification. [Figure 27] Figures 27A-B show XPS of graphite and graphite oxide before and after two cycles of ALD. In Figure 27A, the bottom trace is virgin graphite and the top trace is after the second cycle of ALD, and the top trace is virgin graphite oxide and the top trace is after the second cycle of ALD. Figure 27B shows the absence of a peak in the region corresponding to Pd. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present disclosure will now be described more completely below, although not all embodiments of the present disclosure are shown. Although the present disclosure has been described with reference to exemplary embodiments, those skilled in the art will understand that various changes may be made and elements thereof may be replaced with equivalents without departing from the scope of the present disclosure. In addition, many modifications may be made to adapt a particular structure or material to the teachings of the present disclosure without departing from the essential scope of the present disclosure.

[0019] The drawings accompanying this application are for illustrative purposes only. They are not intended to limit the embodiments of this application. Additionally, the drawings are not drawn to scale. Elements common between the figures may retain the same numerical designations.

[0020] When a range of values ​​is provided, it is understood that each value between the upper and lower limits of that range and any other stated range, or intervening value within that stated range, is encompassed within the invention. The upper and lower limits of these smaller ranges may independently be included in the smaller ranges, which are also encompassed within the invention, as are any specifically excluded limits in a stated range. When a stated range includes one or both of the limits, ranges excluding either or both of those included limits are also included in the invention.

[0021] The following terms are used to describe the present invention. If a term is not specifically defined herein, the term is given its art-recognized meaning by one of ordinary skill in the art applying that term in the context of its use in describing the present invention.

[0022] As used in this specification and the appended claims, the articles "a" and "an" are used herein to refer to one or to more than one (i.e., to at least one) of the grammatical object of the article, unless the context clearly indicates otherwise. By way of example, "an element" means one element or more than one element.

[0023] As used herein in the specification and claims, the phrase "and / or" should be understood to mean "either or both" of the elements so conjoined. That is, in some cases the elements are conjointly present and in other cases they are non-conjoined. Multiple elements listed with "and / or" should be interpreted in the same manner, that is, "one or more" of the elements are so conjoined. Other elements other than the elements specifically identified by the "and / or" clause may optionally be present, whether or not related to those specifically identified elements. Thus, as a non-limiting example, when used in conjunction with open-ended language such as "comprising," a reference to "A and / or B" may, in one embodiment, refer only to A (optionally including elements other than B), in another embodiment, refer only to B (optionally including elements other than A), in yet another embodiment, refer to both A and B (optionally including other elements), and so forth.

[0024] As used herein in the specification and claims, "or" should be understood to have the same meaning as "and / or" as defined above. For example, when separating items in a list, "or" or "and / or" shall be interpreted as inclusive, i.e., including at least one of a number or list of elements, but also including two or more, and optionally including additional items not listed. Only terms clearly indicating the contrary, such as "only one of," or "exactly one of," or, when used in the claims, "consisting of," refer to the inclusion of exactly one element of a number or list of elements. Generally, as used herein, the term "or" shall be interpreted as indicating exclusive alternatives (i.e., "one or the other, but not both") only when preceded by an exclusive term, such as "either," "one of," "only one of," or "exactly one of."

[0025] In the above specification, as well as in the claims, all transitional phrases such as "comprising," "including," "carrying," "having," "containing," "involving," "holding," "composed of," and the like, are to be understood to be open-ended, i.e., to mean inclusive but not limited to. The transitional phrases "consisting of" and "consisting essentially of," alone, shall be closed or semi-closed transitional phrases, respectively, as set forth in Section 2111.03 of the 10 United States Patent Office Manual of Patent Examining Procedures.

[0026] As used herein in the specification and claims, the phrase "at least one," in reference to a list of one or more elements, should be understood to mean at least one element selected from any one or more elements in the list of elements, but not necessarily including at least one of each and every element specifically listed in the list of elements, nor excluding any combination of elements in the list of elements. This definition also allows that elements other than those specifically identified in the list of elements to which the phrase "at least one" refers may optionally be present, regardless of the relevance of those specifically identified elements. Thus, as a non-limiting example, "at least one of A and B (or, equivalently, "at least one of A or B," or, equivalently, "at least one of A and / or B") can refer to, in one embodiment, at least one, in the absence of B (and optionally including elements other than B), optionally including two or more As; in another embodiment, at least one, in the absence of A (and optionally including elements other than A), optionally including two or more Bs; in yet another embodiment, at least one, optionally including two or more As, and at least one, optionally including two or more Bs (and optionally including other elements); etc. It should also be understood that, unless expressly indicated to the contrary, in any method claimed herein that includes two or more steps or actions, the order of the steps or actions of the method is not necessarily limited to the order of the steps or actions of the method recited.

[0027] As used herein, the terms "fluid," "gas" or "gaseous," and "vapor" or "vaporous" are used in a generic sense and are intended to be interchangeable, unless the context indicates otherwise.

[0028] ALD methods, in which a precursor gas is chemisorbed onto the surface of a substrate, require the presence of functional groups (e.g., oxide species) on the surface of the substrate that have the ability to react with the precursor gas and replace the ligands of the precursor gas. Typically, it is desirable to have a sufficient adsorption site density (number of surface functional groups per unit area) on the surface of the substrate to provide a uniform monolayer coverage of the substrate. For example, silicon wafers commonly used in semiconductor manufacturing have silanol groups that uniformly cover the surface, so that when ALD is used to apply metal oxide coatings, saturation of the surface of the silicon wafer substrate with the ALD layer is expected due to the large number of surface silanol groups.

[0029] For porous carbon-based substrates such as activated carbon, the surface is non-uniform and the site density of these functional groups is expected to be non-uniform and smaller than the adsorption site density of commonly used substrates such as silicon wafers, resulting in unexpected precursor chemisorption and partial oxidation for ALD growth. Therefore, to achieve ALD on many carbon-based materials, the surface of the carbon-based material must first be pretreated to modify its interfacial chemistry. For example, it has been demonstrated that ALD can be used to coat carbon nanotubes (CNTs), but surface modification is required for carbon materials prior to the ALD process. Surface functionalization of CNTs is often employed to increase the steric hindrance between adjacent CNTs to facilitate exfoliation and improve solubility. Surface functionalization also potentially provides sites for ALD. Traditional examples of CNT surface modification include chemicals for surface oxidation, annealing with plasma, or non-covalent binding groups (such as surfactants, polymers, or DNA). Another traditional method of surface modification involves depositing metal seeds on the surface by physical vapor deposition. Yet another conventional method used for surface modification of CNTs is treatment with diazonium salts to add aryl or aliphatic groups to their surface. Diazonium salts have also been used to functionalize porous carbon materials, such as activated carbon. U.S. Pat. No. 7,698,191 teaches the use of diazonium salt chemistry on carbon materials to provide organic functional groups. Surface-bound organic functional groups allow for metal deposition on the carbon material via the ALD process. The use of diazonium salts is an effective means of controlling the extent and nature of surface functionality. However, the functionality that can be added by this technique is primarily limited to organic species. Although the addition of functional groups, such as diazonium salt treatment, may be beneficial for CNT exfoliation and also provide functionality for ALD, the additional steric hindrance provided by adding functional groups on the porous substrate may lead to loss of pore volume even prior to ALD.This additional treatment step also introduces additional complexity and reduced atom efficiency in the preparation of the substrate, as well as additional process safety risks posed by many diazonium salts. Thus, it has been surprisingly and unexpectedly discovered that it is possible to use ALD methods to modify heterogeneous porous active adsorbent materials, such as activated carbon, with metal oxides without using surface pretreatment to modify the interfacial chemistry or add surface functional groups. Thus, in any of the aspects or embodiments, the present specification provides processes and methods that exclude any additional steps of treating the substrate containing the active adsorbent material to modify the interfacial chemistry or add surface functional groups, apart from activation.

[0030] Surprisingly and unexpectedly, structures are described herein that demonstrate that an activated adsorbent material, such as activated carbon, can serve as a substrate for ALD. ALD methods, in which a precursor gas is chemisorbed onto the surface of a substrate, require the presence of functional groups (i.e., oxide species) on the substrate surface that have the ability to react with the precursor gas and replace the ligands of the precursor gas. Typically, it is desirable to have a sufficient adsorption site density on the substrate surface to provide uniform monolayer coverage of the substrate. However, in the case of an adsorbent material such as activated carbon, the adsorption site density may be lower than that of commonly used substrates, such as silicon wafers used in ALD methods in the semiconductor industry. Because the adsorption site density may be lower for activated carbon, the substrate surface with metal species may not be saturated and the layer may not be uniform. Thus, it has been surprisingly and unexpectedly discovered that it is possible to use ALD methods to modify an adsorbent material, such as activated carbon, with metal species, such as metal oxides.

[0031] Thus, in any aspect or embodiment, the present specification provides a structure comprising an active adsorbent material, e.g., a porous active adsorbent material, and a metal species deposited thereon. In certain aspects or embodiments, the present specification also provides a structure comprising a substrate comprising an active adsorbent material, e.g., a porous active adsorbent material, and a metal species deposited thereon.

[0032] As used herein, unless the context indicates otherwise, the term "substrate (or material) comprising (or including) an active adsorbent material" refers to a substrate (or material) that is at least about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 109, 109, 109, 110, 111, 112, , 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, or 100 wt. %, including all ranges and subranges therebetween) of active adsorbent material, e.g., a substrate or material comprising a porous active adsorbent material as described herein. For example, if a substrate or material comprises less than 100% by weight of active adsorbent material, the remainder up to 100% by weight can comprise one or more additives known in the art, by way of non-limiting examples, binders, processing aids, or the like.

[0033] When the metal species includes titanium oxide, the structure surprisingly and unexpectedly resembles that of commonly used titanium oxide nanoparticles (e.g., P25 TiO 2 The results demonstrate superior catalytic activity compared to that of 1,3-dihydropyridine (commercially available as Evonik).

[0034] In any of the aspects or embodiments described herein, the substrate of the structure includes an active adsorbent material. The active adsorbent material may include activated carbon, carbonized charcoal, zeolite, clay, porous polymer, foam, porous alumina, porous silica, molecular sieve, kaolin, titania, ceria, or a combination thereof. In any of the aspects or embodiments described herein, the active adsorbent material is activated carbon. The active adsorbent material may be derived from an active adsorbent material precursor. As non-limiting examples, the active adsorbent material precursor may be wood, wood dust, wood flour, cotton linters, peat, coal, coconut, linter, carbohydrates, petroleum pitch, petroleum coke, coal tar pitch, fruit pits, fruit stones, nut shells, nut pits, sawdust, palm, vegetables (such as rice husk or straw), synthetic polymers, natural polymers, lignocellulosic materials, or combinations thereof. Additionally, the active adsorbent material may be produced using a variety of processes, including, but not limited to, chemical activation, thermal activation, or combinations thereof.

[0035] In any of the aspects or embodiments described herein, the activated adsorbent material comprises activated carbon powder. Activated carbon is processed to be highly porous (i.e., have a large number of pores per unit volume), which imparts a high surface area. In any of the aspects or embodiments described herein, the surface of the activated adsorbent material of the substrate is not modified, for example, prior to deposition of metal species using ALD. As used herein, "modification" of the surface of the activated adsorbent material excludes an activation process. The activated adsorbent material can be prepared using an activation process. In any of the aspects or embodiments described herein, the activated adsorbent material is activated carbon. Natural carbon (non-activated carbon) can be activated using an activating agent comprising at least one of phosphoric acid, sulfuric acid, boric acid, nitric acid, oxygenated acid, steam, air, peroxide, alkali hydroxide, metal chloride, ammonia, carbon dioxide, or a combination thereof. Activation conditions, including temperature and pressure, are within the skill of one of ordinary skill in the art. As used herein, "modification" includes reaction with a diazonium salt to add aryl or aliphatic linker groups to a surface substituted with functional groups. In any of the aspects or embodiments described herein, the surface of the active adsorbent material has not been modified by reaction with a diazonium salt to add functionalized aryl or aliphatic linker groups attached to the surface.

[0036] In any of the aspects or embodiments described herein, the activated carbon can be derived from an activated carbon precursor. Activated carbon may be produced from a variety of materials, but most commercially available activated carbon is made from peat, coal, lignite, wood, and coconut shell. Based on the source material, the carbon can have different pore sizes, ash content, surface order, and / or impurity profiles. Coconut shell-based carbon has mostly microporous pore sizes, while wood-based chemically activated carbon has mostly mesoporous or macroporous pore sizes. In a preferred embodiment, the activated carbon comprises activated carbon powder. As non-limiting examples, the activated carbon precursor can be wood, wood dust, wood flour, cotton linters, peat, coal, coconut, lignite, carbohydrates, petroleum pitch, petroleum coke, coal tar pitch, fruit pits, fruit stones, nut shells, nut pits, sawdust, palm, vegetables (such as rice husk or straw), synthetic polymers, natural polymers, lignocellulosic materials, or combinations thereof. Additionally, activated carbon may be produced using a variety of processes including, but not limited to, chemical activation, thermal activation, or a combination thereof.

[0037] In any of the aspects or embodiments described herein, the activated carbon precursor is wood. The activated carbon precursor can be activated by heating the activated carbon precursor and treating it with an added oxidizing agent, such as an exogenously added activating agent (i.e., oxidation), such as carbon dioxide, oxygen, acid, or superheated steam. Exemplary activated carbons include NUCHAR® (Ingevity South Carolina, LLC, South Carolina, USA), which is a chemically activated carbon derived from wood and activated with phosphoric acid.

[0038] Generally, the greater the surface area of ​​an activated carbon, the greater its adsorption capacity. For example, the usable surface area of ​​an activated carbon depends on its pore volume. Since the surface area per unit volume decreases as the individual pore size increases, a large surface area is generally maximized by maximizing the number of pores of very small dimensions and / or minimizing the number of pores of very large dimensions. Pore sizes are defined herein as micropores (pore width < 2.0 nm), mesopores (pore width = 2.0-50 nm), and macropores (pore width > 50 nm, and nominally 50 nm-100 micrometers). Mesopores may be further divided between small mesopores (pore width = 2.0-5 nm) and large mesopores (pore width = 5-50 nm).

[0039] Brunauer-Emmett-Teller (BET) surface can characterize the specific surface area of ​​a material. The active adsorbent material (e.g., activated carbon) preferably has a nitrogen BET surface area of ​​about 600 to about 2300, about 800 to about 1800, or about 1000 to about 1600 m2 / gram. Surface area was measured by nitrogen physical adsorption using the Brunauer-Emmett-Teller (BET) method according to ISO 9277:2010 on a Micromeritics ASAP 2420 (Norcross, GA, USA). Pore volume was determined by nitrogen adsorption porosimetry using a Micromeritics ASAP 2420 (Norcross, GA, USA). Briefly, examples / samples are dried overnight in an oven preset at 105-110°C. The samples are removed and kept in a closed system until the temperature equilibrates with the laboratory. The sample is inserted into the instrument's sample tube and placed on the Micromeritics ASAP 2420 instrument. The sample is degassed in situ before the start of the test. The degassing of the sample is performed at 250° C. and 2 μmHg vacuum. The pore volume is calculated from the P / Po isotherm using the SAIEUS program. The non-ideality factor was 0.0000620. The density conversion factor was 0.0015468. The hard sphere diameter was 3.860 Å. The molecular cross-sectional area was 0.162 nm2. The target relative pressures (in mmHg) for the isotherms were 0.002, 0.005, 0.01, 0.0125, 0.0250, 0.050, 0.075, 0.1, 0.1125, 0.125, 0.150, 0.175, 0.20, 0.25, 0.30, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, and 0.95. At low pressure, the instrument was set to "low pressure incremental dose mode," which instructs the instrument to record data based on incremental doses of an amount of 20.000 cm3 / g STP. Actual points were recorded within absolute or relative pressure tolerances of 5 mmHg or 5%, whichever is tighter, respectively. The time between successive pressure readings during equilibration was 20 seconds. If the ΔP between readings was <0.001%, the data was taken and P was set to the next set point.The minimum delay between data recordings was 600 seconds. Nitrogen adsorption isotherm data were analyzed by the SAIEUS program. The "Max" field for the pore size range was changed to 500. In the L-curve chart, the lambda value was set by scrolling the bar to find the tangent point on the curve. The mathematical model that processes the isothermal data accumulated by the Micromeritics instrument to determine the pore size distribution is described as nonlocalized density functional theory (NLDFT). This model appears to minimize the associated errors in the low pressure range (equalizing small pores) and is described in J. Phys. Chem., 2009, 113, 19382-19385 (by J. Jagiello and JP Olivier).

[0040] As previously discussed, in any of the aspects or embodiments described herein, the active adsorbent material is not additionally modified other than activation. Substrate surface modification can introduce additional surface functional groups to increase the number of functional groups that are covalently bonded to the adsorbent material and have the ability to bind metal species. Alternatively, substrate surface modification can include coating of a material (e.g., a surfactant) that has the ability to bind metal species. Thus, substrate surface modification can increase the adsorption site density of the surface. The surface of an active adsorbent material that has not been further modified after activation can have a lower adsorption site density than the surface of an active adsorbent material that has undergone further surface modification after activation. The ratio of heteroatoms, such as oxygen, nitrogen, and phosphorus, to carbon can be proportional to the adsorption site density of the surface of the active adsorbent material.

[0041] One method of measuring the adsorption site density is surface elemental analysis. Surface analytical techniques can provide information about the chemical composition of a material surface, depending on the analytical method used. The density of elements (e.g., O, N, and P) may be measured, for example, using Boehm titration or Auger electron spectroscopy (AE).

[0042] Another way to measure adsorption site density is bulk elemental analysis within a specified sampling depth from the surface. X-ray photoelectron spectroscopy (XPS) can be used with sampling depths of about 5 nm or less, or about 4 nm or less, or about 3 nm or less, or about 2 nm or less, or about 1 nm or less. XPS is performed to obtain concentrations of carbon, chlorine, fluorine, sodium, nitrogen, oxygen, phosphorus, titanium, and palladium by sprinkling sample powder onto double-sided adhesive tape and removing the excess before introducing into the vacuum chamber. Data were acquired from an analyzed area having a diameter of approximately 1 mm using a monochromated Al Kα X-ray source and a take-off angle of 65°. A low-energy resolution survey scan was obtained from each sample to determine which elements were present. The atomic concentrations of these elements and their local chemistry were determined from multiple scans at higher energy resolution.

[0043] In any of the aspects or embodiments described herein, the bulk oxygen to carbon ratio at a sampling depth of about 5 nm or less is about 0.25 or less, about 0.20 or less, about 0.15 or less, about 0.10 or less, about 0.09 or less, about 0.08 or less, about 0.07 or less, about 0.06 or less, about 0.05 or less, about 0.01 to about 0.25, about 0.01 to about 0.25, about 0.01 to about 0.20, about 0.01 to about 0.15, or about 0.01 to about 0.10, including all overlapping ranges, inclusive ranges and values ​​therebetween.

[0044] In any of the aspects or embodiments described herein, the bulk phosphorus to carbon ratio at a sampling depth of about 5 nm or less is about 0.10, about 0.09, about 0.08, about 0.07, about 0.06, about 0.05 or less, including all overlapping ranges, inclusive ranges and values ​​therebetween.

[0045] In any of the aspects or embodiments described herein, the bulk nitrogen to carbon ratio at a sampling depth of about 5 nm or less is about 0.10, about 0.09, about 0.08, about 0.07, about 0.06, or about 0.05 or less, including all overlapping ranges, inclusive ranges, and values ​​therebetween.

[0046] As used herein, "surface oxygen to carbon ratio" refers to the ratio of surface carbon bonded to oxygen to the total number of surface carbons, which includes unbonded surface carbon, carbon bonded to oxygen, and carbon bonded to other elements or groups. In any of the aspects or embodiments described herein, the surface oxygen to carbon ratio is less than about 1.0, less than about 0.95, less than about 0.90, less than about 0.85, less than about 0.80, less than about 0.75, less than about 0.70, less than about 0.65, less than about 0.60, less than about 0.55, less than about 0.50, less than about 0.45, less than about 0.40, less than about 0.35, less than about 0.30, less than about 0.25, less than about 0.20, less than about 0.15, less than about 0.10, from about 0.01 to less than about 1.0, from about 0.10 to less than about 1.0, from about 0.05 to less than about 1.0, from about 0.01 to less than about 0.95, from about 0.01 from about 0.90, from about 0.01 to less than about 0.85, from about 0.01 to less than about 0.80, from about 0.01 to less than about 0.75, from about 0.01 to less than about 0.70, from about 0.01 to less than about 0.65, from about 0.01 to less than about 0.60, from about 0.01 to less than about 0.55, from about 0.01 to less than about 0.50, from about 0.01 to less than about 0.45, from about 0.01 to less than about 0.40, from about 0.01 to less than about 0.35, from about 0.01 to less than about 0.30, from about 0.01 to less than about 0.25, from about 0.01 to less than about 0.20, including all overlapping ranges, inclusive ranges and values ​​therebetween.

[0047] As used herein, "surface phosphorus to carbon ratio" refers to the ratio of surface carbon bound to phosphorus to the total number of surface carbons. The total number of surface carbons includes unbound surface carbon, carbon bound to phosphorus, and carbon bound to other elements or groups. It is understood that surface phosphorus can be bound to surface carbon via a heteroatom linker (e.g., oxygen). Surface phosphorus can exist in an oxidized or non-oxidized state. In any of the aspects or embodiments described herein, the surface phosphorus to carbon ratio is about 0.33, about 0.30, about 0.25, about 0.20, about 0.15, about 0.10 or less, including all overlapping ranges, inclusive ranges, and values ​​therebetween.

[0048] As used herein, "surface nitrogen-to-carbon ratio" refers to the ratio of surface carbon bonded to nitrogen to the total number of surface carbons. The total number of surface carbons includes unbonded surface carbon, carbon bonded to nitrogen, and carbon bonded to other elements or groups. In any of the aspects or embodiments described herein, the surface nitrogen-to-carbon ratio is about 0.50, about 0.45, about 0.40, about 0.35, about 0.30, about 0.25, about 0.20, about 0.10 or less, including all overlapping ranges, inclusive ranges, and values ​​therebetween.

[0049] As used herein, "oxidized phosphorus surface oxygen-to-phosphorus ratio" refers to the ratio of surface phosphorus atoms that are oxidized to the total number of surface phosphorus atoms, which includes oxidized and non-oxidized phosphorus atoms. In any of the aspects or embodiments described herein, the surface oxygen to phosphorus ratio of the oxidized phosphorus is less than about 1.0, less than about 0.95, less than about 0.90, less than about 0.85, less than about 0.80, less than about 0.75, less than about 0.70, less than about 0.65, less than about 0.60, less than about 0.55, less than about 0.50, less than about 0.45, less than about 0.40, less than about 0.35, less than about 0.30, less than about 0.25, less than about 0.20, less than about 0.15, less than about 0.10, from about 0.01 to less than about 1.0, from about 0.10 to less than about 1.0, from about 0.05 to less than about 1.0, from about 0.01 to less than about 0.95, from about from about 0.01 to less than about 0.90, from about 0.01 to less than about 0.85, from about 0.01 to less than about 0.80, from about 0.01 to less than about 0.75, from about 0.01 to less than about 0.70, from about 0.01 to less than about 0.65, from about 0.01 to less than about 0.60, from about 0.01 to less than about 0.55, from about 0.01 to less than about 0.50, from about 0.01 to less than about 0.45, from about 0.01 to less than about 0.40, from about 0.01 to less than about 0.35, from about 0.01 to less than about 0.30, from about 0.01 to less than about 0.25, from about 0.01 to less than about 0.20, including all overlapping ranges, inclusive ranges and values ​​therebetween.

[0050] The structure includes a metal species deposited on a substrate including an active adsorbent material. The metal species can be derived from a metal species precursor. The metal species precursor can include at least one metal and at least one ligand. The metal species precursor can include at least one metal and at least one ligand that have the ability to be displaced, and the metal can form bonds with functional groups on the surface of the active adsorbent material. The metal species can include a single metal or multiple metals. Metal species include metals such as Li, Be, Mg, Ca, Sr, Ba, Sc, Y, La, Ti, Zr, Hf, Ce, V, Nb, Ta, Pr, Cr, Mo, W, Nd, Mn, Fe, Ru, Sm, Co, Rh, Ir, Ni, Pd, Pt, Gd, Cu, Ag, Zn, Cd, B, Al, Ga, In, Si, Sn, Pb, P, Sb, and Bi; metal oxides such as titanium oxide, copper oxide, cerium oxide, phosphorus oxide, hafnium oxide, aluminum oxide, zirconium oxide, zinc oxide, silicon oxide, tantalum oxide, tungsten oxide, and vanadium oxide; 3 Formula (CaTiO 3 vanadium phosphide (VPO), FePO 4 metal oxide phosphates or metal phosphates, such as phosphates, silica phosphates, and silica phosphates; multimetal oxides, such as molybdates, tungstates, antimonates, and vanadates; noble metals and noble metal compounds, such as Ru, Pt, Pd, and PdO; organometallic compounds, such as metal sulfides, metal nitrides, metal phosphides, and metal alkyl compounds, cyclopentadienyl compounds, and metallocenes (e.g., Al(CH)). 3 ) 3 , MeCpPtMe 3 , ferrocene), or any combination thereof. In any of the aspects or embodiments described herein, the metal precursor comprises palladium hexafluoro-acetylacetonate or bis(2,2,6,6-tetramethyl-3,5-heptanedionato)palladium(II).

[0051] The metal species deposited on the surface of the active adsorbent material can be in the form of a layer or coating. As used herein, the terms "film", "layer" and "coating" include complete films, layers or coatings (i.e., continuous) as well as partial films, layers or coatings (i.e., incomplete or not continuous or uniform). The layer containing the metal species can be disposed directly on the surface of the substrate without an intervening layer. The structure can include a single layer or multiple layers. In any of the aspects or embodiments described herein, the structure includes 0-10 layers, 1-10 layers, 0-5 layers, 1-5 layers, 2-10 layers, 2-8 layers, 2-5 layers, or 2-4 layers.

[0052] The structure may comprise about 0.1 to about 50% by weight, or about 0.5 to about 50% by weight, of the metal of the metallic species, based on the total weight of the structure. The structure may comprise about 0.5 to about 45% by weight, about 0.5 to about 40% by weight, about 0.5 to about 35% by weight, about 0.5 to about 30% by weight, about 0.5 to about 25% by weight, about 0.5 to about 20% by weight, about 0.5 to about 15% by weight, about 0.5 to about 10% by weight, or about 0.5 to about 5% by weight of the metal of the metallic species, based on the total weight of the structure. In any of the aspects or embodiments described herein, when the structure comprises titanium(IV) oxide as the metallic species, the structure comprises about 0.5 to about 50% by weight of titanium, based on the total weight of the structure.

[0053] The structures are not limited to any application. Non-limiting examples of applications of the structures disclosed herein include catalytic, filtration, antibacterial, antifungal, photovoltaic, antifungal, chemisorption, antiviral, textile, ceramic, biotechnology, biomedical, fuel cell systems, semiconductor, microelectronics, optical, and gas storage applications.

[0054] In an additional aspect, the present disclosure provides a method of preparing a structure by a process comprising: (a) providing a substrate comprising an active adsorbent material, e.g., a porous active adsorbent material (e.g., activated carbon), in a reactor; and (b) performing or carrying out at least one atomic layer deposition cycle to deposit a metal species, e.g., a metal oxide, the at least one atomic layer deposition cycle comprising: (i) introducing a first precursor gas into the reactor to provide a metal species precursor to be deposited on a surface of the active adsorbent material; and (ii) introducing a second precursor gas into the reactor to provide the structure. In any aspect or embodiment, step (b) is repeated from 2 to about 10 times.

[0055] In any aspect or embodiment described herein, the structure prepared by atomic layer deposition (ALD) is a porous metal-coated structure.

[0056] The first precursor gas may include at least one metal and at least one ligand. At least one ligand may have the ability to be replaced by a surface functional group of the active adsorbent material. At least one ligand may have the ability to be replaced by an atom provided by the second precursor gas (e.g., O, H). In any of the aspects or embodiments described herein, the first precursor gas includes organometallic compounds such as metal halides, metal oxyhalides, metal alkoxides, metal alkyl compounds (e.g., Al(CH3)3), metal alkene compounds, metal alkyne compounds, cyclopentadienyl compounds (e.g., MeCpPtMe3), and metallocenes (e.g., ferrocene), hexafluoro-acetylacetonate, or combinations thereof. In any of the aspects or embodiments described herein, the first precursor gas includes titanium chloride, titanium oxychloride, titanium alkoxide, or combinations thereof. In any of the aspects or embodiments described herein, the first precursor gas includes hexafluoro-acetylacetone.

[0057] The second precursor gas can replace (e.g., oxidize, reduce) at least one ligand of the metal species precursor deposited on the surface of the active adsorbent material. The second precursor gas can be a nitrogen-containing precursor gas (such as ammonia, 1,1-dimethylhydrazine, tert-butylamine, or allylamine), a sulfur-containing precursor gas (such as hydrogen sulfide), an oxygen-containing precursor gas (such as H 2 O, H 2 O 2 , O 2 , O 3 , or alcohol), a phosphorus-containing precursor gas (phosphine gas or P(O)OMe 3 The second precursor gas may include a fluorine-containing gas (such as hydrogen), a hydrogen-containing gas (such as hydrogen gas), formalin, or a combination thereof. In any of the aspects or embodiments described herein, the second precursor gas may replace at least one ligand of a metal halide, a metal oxyhalide, a metal alkoxide, or a combination thereof. In an exemplary embodiment, the second precursor may replace at least one halogen of a metal halide. The second precursor gas may include an oxidizing agent. The second precursor gas may include a reducing agent. In any of the aspects or embodiments described herein, the second precursor gas may include H 2 O, H 2 O 2 , O 2 , O 3 , N 2 O, NO, NO 2 , N.H. 3 , ammonia, 1,1-dimethylhydrazine, tert-butylamine, or allylamine, alcohol, PH 3 , P(O)OMe 3 , hydrogen sulfide, H2, ambient air, formalin, or a combination thereof.

[0058] In any of the aspects or embodiments described herein, the first precursor gas comprises palladium hexafluoro-acetylacetonate and the second precursor gas comprises formalin. In any of the aspects or embodiments described herein, the first precursor gas comprises bis(2,2,6,6-tetramethyl-3,5-heptanedionato)palladium(II) and the second precursor gas comprises ambient air.

[0059] In the method of the present disclosure, step b can be carried out at least twice, or from 2 to 4 times.

[0060] The method is generally carried out under vacuum pressure. The vacuum pressure is selected such that the first precursor gas is a solid or liquid (and does not substantially vaporize) at room temperature. The first precursor can be heated to produce a first precursor gas. The second precursor can be heated to produce a second precursor gas. In an alternative embodiment, the second precursor gas is ambient air. The reactor can be opened to the atmosphere to expose the metal species precursor in the reactor to the ambient air to oxidize the metal species precursor to the metal species. The method can include combinations of the above.

[0061] The method can include introducing an additional second precursor gas that is different from the second precursor gas introduced in step (b)(ii) of the method of the present disclosure. The additional second precursor gas can be used to convert a functional group attached to the metal of the metallic species to a different functional group.

[0062] The method may also include a purging step following step (b)(i) in which the first precursor gas is introduced, step (b)(ii) in which the second gas is introduced, or a combination thereof. Purging may be performed using a vacuum, using an inert gas, or a combination thereof. The purging step may remove unreacted precursor gas and by-products from the reaction of the first precursor gas with the active adsorbent material and / or the reaction of the second precursor gas with the metal species precursor deposited on the surface of the active adsorbent material.

[0063] In any aspect or embodiment described herein, a method for preparing a modified activated adsorbent material includes: (a) providing activated carbon in a reactor; and (b) performing at least one atomic layer deposition cycle, the performing at least one atomic layer deposition cycle including: (i) introducing TiCl4 gas into the reactor; and (ii) introducing water vapor into the reactor to provide a titanium oxide modified activated carbon.

[0064] The titanium dioxide modified activated carbon powder was AEROXIDE® P25 TiO as determined according to 2-propanol temperature programmed desorption (TPD) spectrum. 2 (commercially available from Evonik, Hanau-Wolfgang, Germany). For a more detailed description, see Yi Y. Wu, Harold H. Kung, Probing properties of the interfacial perimeter sites in TiOx / Au / SiO 2 with 2-propanol decomposition, Applied Catalysis A: General, Volume 548, 2017, Pages 150-163.

[0065] TPD of 2-propanol has been widely used to characterize oxide surfaces. 2-propanol has been widely observed to disproportionate on oxide surfaces, both by dehydrogenation to acetone and dehydration to propene. 2 The catalytic activity of was characterized by comparing the yields of acetone and propene with those from P25.

[0066] In any of the described aspects or embodiments, the atomic layer deposition apparatus comprises a vacuum manifold, a container for each of the first precursor, the second precursor, and the activated carbon, a vacuum pump, a cold trap, at least one heat source, and a heating controller. The vacuum manifold includes lines with valves connected to the manifold for the first precursor gas, the second precursor gas, and the activated carbon substrate; and containers for each of the first precursor, the second precursor, and the activated carbon substrate, each connected to a respective line of the manifold. The manifold and containers can be heated for efficient transfer of the precursor gas to the activated carbon.

[0067] In any of the aspects or embodiments described, the atomic layer deposition method can be carried out in an apparatus suitable for batch mode, semi-continuous mode, continuous mode, or a combination thereof. In any of the aspects or embodiments described herein, the apparatus comprises a fluidized bed reactor. Of course, the structures can be formed using any of the apparatuses known to those skilled in the art. EXAMPLES

[0068] Unless specifically stated otherwise, the amount of each component is in weight percent (wt %) based on the total weight of the composition.

[0069] The bulk nitrogen-to-carbon, phosphorus-to-carbon, and oxygen-to-carbon ratios of the substrates may be measured using energy dispersive spectroscopy (EDS). EDS Spectra was provided by Electral Analysis, Inc (Lexington, KY, USA). Each sample was affixed to carbon tape. Spectra were obtained using an Oxford X-Max 80 energy dispersive spectrometer at three different sites for each sample analyzed. Spectra were acquired at 500× and 1,000× with an excitation voltage of 30 kV. Surface oxygen density may be measured using Boehm titration, Auger electron spectroscopy (AE), X-ray photoelectron spectroscopy (XPS), or low energy ion scattering (LEIS). Metal loading may be measured using Auger electron spectroscopy (AE), atomic absorption spectroscopy (AAS), energy dispersive spectroscopy (EDS), inductively coupled plasma spectroscopy (ICP), LEIS, or XPS.

[0070] [Example 1] Activated carbon powder TiO 2 ALD and catalyst characterization Example 1 is TiO on activated carbon powder 2 We describe the ALD of TiO 2 The activated carbon powder was NUCHAR® RGC (Ingevity South Carolina, LLC, North Charleston, South Carolina, USA) and had a d50 of 18.3 microns. 2 The powder was AEROXIDE® P25 (Evonik, Hanau-Wolfgang, Germany) and had a d50 of 2.95. The ALD apparatus was constructed consistent with FIG. 1. The apparatus includes a vacuum manifold, a cold trap (104), a vacuum pump (105), and three source lines with valve controls (107, 108, 109). The three source lines were used to carry the reaction precursors: activated carbon, TiCl 4The flask was connected to flasks (101, 102, and 103) for titanium (IV chloride 99.9%, obtained from Sigma Aldrich), and oxidant (water). The manifold was covered with heating tape so that the manifold temperature was 200° C. Activated carbon (2 g) was loaded into the flask, the flask was connected to a vacuum manifold, and TiCl 4 The activated carbon was heated at 150 °C for 2 h for about 10 min to allow the deposition of β-acetylglucosamine and partial oxidation at the active sites to proceed unhindered. -3 The chamber was evacuated at a vacuum pressure of 10 Torr to remove contaminants. 2 If O remains on the surface, TiCl 4 The TiCl2 was then cooled to room temperature, removed from the vacuum, and weighed to record the weight loss. The flask was then attached to a manifold and allowed to evacuate overnight at room temperature. 4 (5 mL) was added to a vial connected to a vacuum manifold. The vapor space in the vial was evacuated three times to allow the contents of the vial to equilibrate between vacuum pulses. 4 Steam (heated to 80° C.) was introduced into the reaction flask containing the activated carbon at 150° C. by opening valves 108, 109, and 110, which resulted in a vacuum of less than 50 mTorr. Valve 110 was closed after 5 seconds. After 2 hours, valve 108 was closed and valve 110 was slowly reopened. The reaction flask was evacuated for 2 hours. The manifold was removed from the vacuum so that it was open to air. The vial containing the water was heated to 60° C. and valves 107, 109, and 110 were opened to allow moist air to flow across or through the reaction flask. After 2 hours, the heat was removed and the manifold was left open to air overnight. The process was repeated three more times.

[0071] Figure 2 shows the results of gravimetric analysis of activated carbon powder modified with titanium oxide after 1–4 cycles of ALD.

[0072] 3A-3D show the TiO 2 The weight percentages are shown.

[0073] 4A-4D are SEM images of titanium oxide modified activated carbon powder after 0-4 ALD cycles.

[0074] Figure 5 shows the TiO2 deposition rate for titanium dioxide modified activated carbon powder through four ALD cycles. 2 The growth rate is shown.

[0075] TiO using temperature programmed desorption 2 Methods for characterizing modified RGCs.

[0076] TiO 2 To characterize the catalytic activity of modified RGC carbon samples, an internal temperature programmed desorption setup and technique was developed. The TPD setup consisted of a GC-MS (Shimadzu GCMS-QP2010S) connected to the exhaust port of a thermogravimetric analyzer (Perkin Elmer TGA 8000). The column in the GC-MS was bypassed and the exhaust gas was directly injected into the GC-MS for real-time analysis of the TGA products. The samples were loaded into the TGA and saturated with 2-propanol. The 2-propanol saturated samples were run at 20 ml / min N 2 The mixture was kept in a 0.5 mL flask at 25° C. for 30 min to remove excess 2-propanol. The sample was heated at 10° C. / min while simultaneously monitoring the desorption products using GC-MS.

[0077] TiO 2 Modified RGC and commercial P25 TiO 2were tested using the characterization methods described above. The 2-propanol temperature programmed desorption spectra (TPD spectra) of each are shown in Figures 6A-6C. The desorption peaks were integrated to quantitate the product yields. The desorption products were identified by their characteristic fragmentation patterns. The calculated mass spectrometer sensitivity factors were used to quantitate the product yields. The characteristic masses (m / z) used to quantitate the products from 2-propanol TPD were 45 (2-propanol), 18 (H 2 A comparison of the product spectra from 2-propanol TPD is shown in Figure 7A-B. The acetone and propene yields from the TPD method are summarized in Table 1, and the TiO yields after four rounds of ALD are shown in Table 2. 2 The superior performance of the modified RGC is shown.

[0078] [Table 1]

[0079] [Example 2] TiO on granular activated carbon 2 ALD Example 2 shows TiO on several activated carbons and graphite. 2The ALD of 1,2,3,4-trifluoroethylene (1,1,2,3,4-trifluoroethylene) is described. All activated carbons and graphite were screened to a particle size of 20 × 60 mesh. Activated carbons included chemically activated, wood-based carbons from NUCHAR® (Ingevity South Carolina LLC, North Charleston, SC, USA). These carbons were NUCHAR® RGC, NUCHAR® AquaGuard (AG), NUCHAR® BAX 1500, and NUCHAR® WV-A 1100. Thermally activated, coconut-based carbons (20 × 50 mesh, acid washed, 85-90 CTC (Carbon Activated Corp, Compton, CA, USA), and graphite (SAG20 (MTI ALD carbon was also used. For testing with oxidized samples, both graphite and RGC were oxidized by placing the respective carbons in a beaker containing 70% nitric acid (Sigma-Aldrich). The ratio of carbon to nitric acid was 1:10. The beaker containing the acid and carbon was heated to 80° C. and then stirred for 3 hours. The carbon was then removed from the acid using vacuum filtration. The filtered carbon was washed using distilled water until the pH was >5. The carbon was then placed in an oven at 110° C. overnight. Table 2 shows the BET surface area and pore volume for each of these carbons. Prior to subjecting the carbons to ALD, the carbons were analyzed by XPS for C, O, N, and P content, and the results are shown in FIG. 10 and summarized in Table 3. FIGS. 9A-9C show SEM photos of unused WV-A1100 (FIG. 9A), BAX1500 (FIG. 9B), and graphite (FIG. 9C).

[0080] [Table 2]

[0081] [Table 3]

[0082] An ALD apparatus was constructed consistent with FIG. 8. The apparatus included a heated source line with valve control in series with a vacuum pump. To generate humid air, the source line was connected to a steam generator connected to a syringe filled with water. Air was introduced into the heat trace line. As shown in FIG. 8, TiCl 4 was in one column and carbon was in the second column. Prior to deposition, the apparatus was heated at room temperature for about 10 min by closing valve 906 and opening valves 908 and 909. -3 The traced lines were heated to 200 °C and then dried with TiCl 4 The columns containing TiCl and carbon were heated to 80°C and 150°C, respectively. 4 To deposit 100% CO on the carbon, valve 909 was closed and valves 907 and 908 were opened for 2 hours. After 2 hours, valve 907 was closed and valve 909 was slowly reopened. The apparatus was allowed to evacuate for 2 hours. Valve 906 was then opened to allow moist air to flow through the carbon column. After 2 hours, the heat was removed and the manifold was left open to air overnight. The process was repeated one more time, but can be repeated 2-4 times.

[0083] TiO 2 After two cycles of ALD with, the estimated surface coverage was calculated assuming monolayer coverage according to the following equation: (e.g., rho and a).

number

[0084] In the formula, ρ TiO2 TiO 2 where SA is the BET surface area (m / g) of carbon and α is the TiO 2 is the characteristic length (lattice parameter, m) of the unit cell of

[0085] FIG. 11 shows a comparison of the estimated surface coverage of coconut, oxidized RGC, RGC, WVA1100, AquaGuard (AG), and graphite after varying ALD cycles. For the estimates presented in this figure, TiO 2 is assumed to be deposited as the rutile phase. 2 The ALD rate is shown to be highest for coconut and follows the order coconut > oxidized RGC, Aquaguard, WV-A 1100 RGC > graphite. In addition, the surface oxidation is enhanced by the TiO 2 enhanced deposition rate (comparing oxidized RGC to RGC).

[0086] 12A to 12C show the TiO 2 SEM and XRD images of oxidized RGC, AG, and graphite after ALD. The oxidized RGC has a higher TiO content compared to the AG (non-oxidized). 2 The graphite had the incorporation of TiO 2 The incorporation was very poor.

[0087] Figure 13 shows TiO 2 Figure 1 shows XPS spectra of WV-A 1100 before and after ALD. The virgin material is the bottom trace, the material after one cycle of ALD is the middle trace, and the material after two cycles of ALD is the top trace.

[0088] Figure 14 shows the TiO 2 XPS spectra of coconut, 1100, and RGC after ALD, respectively. RGC after two ALD cycles is the bottom trace, 1100 after two ALD cycles is the next highest trace, and coconut after two ALD cycles is the top trace. The O1s peaks correspond to metal oxides. The Ti(2p) peaks at 2p3 / 2 and 2p1 / 2 correspond to fully oxidized Ti atoms (TiO 2 Formation).

[0089] Figure 15 shows TiO 2Butane isotherm results for WVA1100 before and after ALD are shown. FIG. 15A shows the isotherm results based on the total weight of the sample. The virgin material is the top trace, the material after one cycle of ALD is the middle trace, and the material after two cycles of ALD is the bottom trace. After normalizing on a carbon weight basis, there is a substantial overlap of the plots for virgin, one cycle, and two cycle materials, as shown in FIG. 15B.

[0090] [Example 3] TiO using temperature programmed desorption (TPD) 2 Catalytic characterization of modified granular carbons. TiO 2 An internal desorption setup and technique was developed to test the catalytic activity of the modified carbon samples. The TPD setup included a GC-MS (SHIMADZU GCMS-QP2010S) connected to the exhaust port of a thermogravimetric analyzer (PERKIN ELMER TGA 8000). The column in the GC-MS was bypassed and the exhaust gas was directly injected into the mass spectrometer for real-time analysis of the TGA products. The sample was loaded into the TGA and saturated with 2-propanol. Nitrogen (g) was passed at 20 mL / min for 30 min at 25° C. to remove excess 2-propanol and heated at 10° C. / min while simultaneously monitoring the desorption products in the mass spectrometer. The desorption products were identified by their characteristic fragmentation patterns. The product signals were corrected by their sensitivity factors. The characteristic masses (m / z) used to quantify the products from 2-propanol were 45 (2-propanol), 18 (H 2 O), and 41 (propene).

[0091] 16A-16B show the results of two-cycle TiO 2 16A-16B show the TPD spectra after ALD. For each of Figures 16A-16B, the spectrum of the ALD modified material is overlaid with the spectrum of the virgin material. 2The lower curve for propene is for material subjected to one cycle of ALD, and the upper curve for acetone, CO after a second cycle of ALD. 2 , and propene, respectively.

[0092] Figure 17 shows TiO 2 Figure 1 shows the TPD spectrum of the modified graphite: no reaction products were detected and rapid desorption was observed due to the lack of porosity in the material.

[0093] Figure 18 shows TiO 2 Figure 1 shows the TPD spectrum of modified AQUAGUARD. The peak at 120 indicates a reactive intermediate, where the oxygen of 2-propanol is bonded to titanium.

[0094] Figure 19 shows TiO 2 Figure 1 shows the TPD spectrum of the modified oxidized RGC. Acetone and propene reaction products were detected.

[0095] [Example 4] Palladium deposition on WV-A 1100 Pd deposition was carried out using palladium hexafluoro-acetylacetonate as the first precursor gas. The sample oven was set to 110° C., the carbon sample was placed in the sample column, and the line heater was set to 180° C. and evacuated for 2 hours. The sample oven and line heater were cooled to 70° C. Palladium hexafluoro-acetylacetonate was added to the sample column. Vacuum pressure was re-established by opening valve 909 for 2 minutes. At this point, valve 909 was closed and precursor deposition was allowed to occur for 30 minutes. After deposition, valve 909 was reopened and the sample was evacuated using the following temperature ranges and times: (1) 30 minutes deposition at 70° C., (2) 30 minutes at 70° C., 30 minutes at 110° C., 2 hours at 180° C. The line heater was heated to 180° C. and the sample oven was left at 180° C. The sample column was then vented to atmosphere by opening valves 906 and 908, and 37% formalin (second precursor gas) was pumped through the vapor generator with nitrogen flow set at 500 sccm. The formalin was pumped through the system for 1 hour. Upon completion, the sample was removed and placed in a 110° C. oven overnight.

[0096] 20A-20C show SEM micrographs and XRD of WV-A 1100 after 1 Pd ALD cycle (FIG. 20A), 2 ALD cycles (FIG. 20B), and 4 ALD cycles (FIG. 20C).

[0097] FIG. 21 shows the XPS of Pd-modified samples of WV-A 1100 after 1, 2, and 4 cycles of ALD. The bottom trace is virgin material, the next trace above is after 1 cycle of ALD, the next trace above is after 2 cycles of ALD, and the top trace is after 4 cycles of ALD. The peak at 339.8 corresponds to Pd. It is clear that the peak at 335.8 eV increases with the number of ALD cycles.

[0098] FIG. 22 shows the wt % Pd deposited on WV-A1100 after 1 (1.29 wt %), 2 (2.84 wt %), and 4 cycles (5.21 wt %) of ALD.

[0099] The activity of the catalyst was tested in reaction with abietic acid. Abietic acid has been shown to be readily converted to dehydroabietic acid in the presence of a conventional Pd catalyst (Linlin Wang, Xiaopeng Chen, Wenjing Sun, Jiezhen Liang, Xu, Zhangfa Tong, Kinetic model for the catalytic disproportionation of pine oleoresin over Pd / C catalyst, Industrial Crops and Products, Volume 49, 2013, pp. 1-9). The catalytic activity of the deposited Pd was characterized by evaluating the rate of disappearance of abietic acid and the rate of formation of the corresponding dehydroabietic acid, and Figure 23 shows the disappearance of abietic acid over time. The two overlapping curves are the reaction without catalyst and the reaction of unused material. The bottom curve corresponds to the reaction of abietic acid in the presence of Pd modified material (i.e. catalyst) obtained after two cycles of ALD. The upper curve, corresponding to the reaction of abietic acid in the presence of Pd-modified material (i.e., catalyst), was obtained after one cycle of ALD.

[0100] The activity of the catalyst (i.e., Pd deposited on WV-A 1100) was tested in an alcohol dehydrogenation reaction with 2-propanol. Figure 24A shows the TGA spectrum using air and N2. Figure 24B shows the evolved gas spectrum.

[0101] [Example 5] Palladium deposition on other carbons Pd deposition was carried out as described in Example 4.

[0102] Figure 25A shows an SEM image of graphite after two cycles of Pd ALD at 10,000x magnification, and Figure 25B shows an SEM image of graphite after two cycles of Pd ALD at 100,000x magnification.

[0103] Figure 26A shows an SEM image of graphite oxide after two cycles of Pd ALD at 10,000x magnification, and Figure 26B shows an SEM image of graphite after two cycles of Pd ALD at 100,000x magnification.

[0104] FIG. 27A-B show XPS of graphite and graphite oxide before and after two cycles of ALD. The bottom trace is virgin graphite and the upper trace is after the second cycle of ALD (FIG. 27A). Similarly, the upper trace is virgin graphite oxide and the upper trace is after the second cycle of ALD (FIG. 27A). FIG. 27B shows the absence of a peak in the region corresponding to Pd. The lack of a detected Pd peak indicates the failure of deposition of Pd via ALD on both graphite oxide and graphite.

[0105] The PIXE analysis of the Pd modified carbon samples is summarized in Table 4 below.

[0106] [Table 4]

Claims

1. 600m 2 / g~2500m 2 1. A structure comprising: an activated carbon adsorbent material substrate having a Brunauer-Emmett-Teller (BET) surface area of ​​1.0 / g and a surface oxygen to carbon ratio based on a total number of surface carbons of 1 or less; and a metal-containing material deposited thereon; The metal-containing material comprises a metal, a metal oxide, or a combination thereof.

2. The structure of claim 1 , wherein the metal-containing material deposited thereon is a film, layer, or coating.

3. 3. The structure of claim 1 or 2, wherein the activated carbon adsorbent material has not been additionally modified other than by activation.

4. The structure of any of claims 1 to 3, wherein the activated carbon adsorbent material comprises activated carbon in powder, granule, pellet, monolith, or honeycomb form.

5. 5. The structure of claim 4, wherein the activated carbon is derived from at least one of wood, wood dust, wood flour, cotton linters, peat, coal, coconut, lignite, carbohydrates, petroleum pitch, petroleum coke, coal tar pitch, fruit pits, fruit stones, nut shells, nut pits, sawdust, palm, vegetables, synthetic polymers, natural polymers, lignocellulosic materials, or combinations thereof.

6. 6. The structure of claim 4 or 5, wherein the activated carbon is activated using an activation comprising at least one of phosphoric acid, sulfuric acid, boric acid, nitric acid, oxygenated acids, steam, air, peroxides, alkali hydroxides, metal chlorides, ammonia, carbon dioxide, or combinations thereof.

7. The structure of any of claims 1 to 6, wherein the active adsorbent material is characterized by a mesoporous pore size, a macroporous pore size, or a combination thereof.

8. 8. The structure of any of claims 1 to 7, wherein the active adsorbent material is characterized by a nitrogen B.E.T. surface area of ​​800 to 1800, or 1000 to 1600 square meters per gram.

9. The structure of any of claims 4 to 8, wherein the activated carbon has a bulk oxygen to carbon ratio of 0.25 or less at a depth of less than 5 nm.

10. The structure of any of claims 4 to 9, wherein the activated carbon has a bulk phosphorus to carbon ratio of 0.10 or less at a depth of less than 5 nm.

11. The structure of any of claims 4 to 10, wherein the activated carbon has a bulk nitrogen to carbon ratio of 0.15 or less at a depth of less than 5 nm.

12. 12. The structure of any of claims 4-11, wherein the activated carbon has a surface phosphorus to carbon ratio of 0.33 or less, based on the total number of surface carbons.

13. 13. The structure of any of claims 4 to 12, wherein the activated carbon has a surface nitrogen to carbon ratio of 0.5 or less, based on the total number of surface carbons.

14. 14. The structure of any of claims 4-13, wherein the activated carbon has a surface oxygen to phosphorus ratio of oxidized phosphorus of 1.0 or less, based on the total number of surface phosphorus atoms.

15. 15. The structure of claim 1 or 14, wherein the metal-containing material is derived from a metal-containing material precursor comprising at least one metal and at least one ligand.

16. The structure of claim 1 , wherein the metal-containing material comprises titanium oxide.

17. The structure of claim 1 , wherein the metal-containing material comprises palladium.

18. 18. The structure of claim 1, 16, or 17, wherein the structure comprises 0.5 to 50 weight percent of the metal-containing material, based on the total weight of the structure.

19. a. providing an active adsorbent material in a reactor; b. performing at least one atomic layer deposition cycle to deposit a metal-containing material, the performing of the at least one atomic layer deposition cycle comprising: i. introducing a first precursor gas into the reactor to provide a metal-containing material precursor deposited on a surface of the active adsorbent material; ii. introducing a second precursor gas into said reactor to provide said structure, A method for manufacturing the structure of claim 1.

20. 20. The method of claim 19, wherein step b is performed 2 to 10 times.

21. 21. The method of claim 19 or 20, further comprising a step comprising purging the reactor after step (b)(i), step (b)(ii), or a combination thereof.

22. The method according to any of claims 19 to 21, wherein the first precursor gas comprises at least one metal and at least one ligand.

23. The method of any of claims 19 to 22, wherein the first precursor gas comprises a metal halide, a metal oxyhalide, an organometallic compound, or a combination thereof.

24. The method of any of claims 19 to 23, wherein the second precursor gas has the ability to replace ligands of the metal-containing material precursor deposited on the surface of the active adsorbent material.

25. The second precursor gas is H 2 O, H 2 O 2 , O 2 , O 3 , N 2 O, NO, NO 2 , N.H. 3 , ammonia, 1,1-dimethylhydrazine, tert-butylamine or allylamine, alcohol, pH 3 , P(O)OMe 3 , hydrogen sulfide, H 2 25. The method of any of claims 19 to 24, comprising: ambient air, formalin, or a combination thereof.

26. 26. The method of any of claims 19 to 25, wherein the active adsorbent material is derived from at least one of wood, wood dust, wood flour, cotton linters, peat, coal, coconut, lignite, carbohydrates, petroleum pitch, petroleum coke, coal tar pitch, fruit pits, fruit stones, nut shells, nut pits, sawdust, palm, vegetables, synthetic polymers, natural polymers, lignocellulosic materials, or combinations thereof.

27. 20. The method of claim 19, wherein the adsorbent material comprises activated carbon in powder, granule, pellet, monolith, or honeycomb form.

28. 28. The method of claim 27, wherein the activated carbon has a bulk oxygen to carbon ratio of 0.25 or less at a depth of less than 5 nm.

29. 29. The method of claim 27 or 28, wherein the activated carbon has a bulk phosphorus to carbon ratio of 0.10 or less at a depth of less than 5 nm.

30. 30. The method of any of claims 27 to 29, wherein the activated carbon has a bulk nitrogen to carbon ratio of 0.15 or less at a depth of less than 5 nm.

31. 31. The method of any of claims 27 to 30, wherein the activated carbon has a surface phosphorus to carbon ratio of 0.33 or less, based on the total number of surface carbons.

32. 32. The method of any of claims 27 to 31, wherein the activated carbon has a surface nitrogen to carbon ratio of 0.5 or less, based on the total number of surface carbons.

33. 33. The method of any of claims 27 to 32, wherein the activated carbon has a surface oxygen to phosphorus ratio of oxidized phosphorus of 1.0 or less, based on the total number of surface phosphorus atoms.

34. a. providing activated carbon powder in a reactor; b. performing at least one atomic layer deposition cycle to deposit a metal-containing material comprising titanium oxide, the performing of the at least one atomic layer deposition cycle comprising: i. Add TiCl into the reactor 4 introducing a gas to provide titanium chloride deposited on the surface of the activated carbon powder; 20. The method of claim 19, comprising the step of: (ii) introducing water vapor or ambient air into the reactor to provide the titanium oxide deposited on the surface of the activated carbon powder.

35. a. the metal-containing material comprises palladium; b. the first precursor gas is palladium hexafluoro-acetylacetone; c. the second precursor gas is formalin or ambient air; or 20. The method of claim 19, wherein the method is at least one of: a.

36. a. providing activated carbon powder in a reactor; b. performing at least one atomic layer deposition cycle to deposit a metal-containing material comprising palladium, the performing of the at least one atomic layer deposition cycle comprising: i. introducing bis(2,2,6,6-tetramethyl-3,5-heptanedionato)palladium(II) into the reactor to provide a palladium intermediate deposited on the surface of the activated carbon powder; ii. introducing ambient air into a reactor to provide said palladium deposited on said surface of said activated carbon powder.

Citation Information

Patent Citations

  • Nanoscale gold catalysts, activators, support media, and related methods useful for making such catalyst systems, particularly gold deposited onto support media using physical vapor deposition.

    JP2007506548A

  • Generation of nanostructured layers by continuous screw dislocation growth

    JP2009508700A

  • Filter element for decomposing pollutants, system for decomposing pollutants, and method of using the system

    JP2016530908A

  • Methods for improving catalytic activity

    JP2019505361A

  • Atomic Layer Deposition of Electrochemical Catalysis

    JP2019529702A